Smart-shaming, Language Anxiety, and Self-Efficacy Among Criminology Students in a Private University - Agayo, Johanna; Batayon, John Carlo; Lleno, Joelinda; Nacion, Princess Dianne; Galicia, Leomar (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the levels and relationships of smart-shaming, language anxiety, and self-efficacy in English-language learning among criminology students in a private university in Laguna, Philippines. It was anchored in Foreign Language Anxiety Theory, Self-Efficacy Theory, and Social Cognitive Theory, which explain the interaction of social experiences, emotional responses, and cognitive beliefs in shaping classroom participation. A quantitative descriptive-correlational research design was employed. The respondents were 138 criminology students from different year levels selected through stratified random sampling with proportional allocation. Data were gathered using a validated and pilot-tested 30-item questionnaire administered through a four-point Likert scale. Weighted mean and standard deviation were used to determine the levels of the variables, while Pearson’s r moment correlation coefficient was used to examine their relationships. The findings revealed a low level of smart-shaming, with an overall weighted mean of 2.12, indicating that peer ridicule and negative labeling occurred minimally. However, the respondents demonstrated high language anxiety, with an overall weighted mean of 2.65, particularly in speaking situations and performance evaluation. They also exhibited high self-efficacy, with an overall weighted mean of 2.92, especially in task completion and persistence. The relationships between smart-shaming and language anxiety, smart-shaming and self-efficacy, and language anxiety and self-efficacy were very weak or negligible and statistically non-significant. Thus, the null hypotheses were not rejected. The study concluded that students could experience considerable English-language anxiety while maintaining confidence and persistence in completing academic tasks. Educators were encouraged to sustain supportive classrooms, use gradual and low-stakes speaking activities, and provide structured communication exercises such as role-playing, mock interviews, and case presentations. The study supports SDG 3: Good Health and Well-Being by addressing anxiety and psychosocial well-being and SDG 4: Quality Education by promoting inclusive and supportive learning environments. Its sustainability impact lies in strengthening educational practices, student well-being, communication development, and institutionally responsive support programs.
Keywords: Criminology Students; English-Language Learning; Language Anxiety; Self-Efficacy; Smart-Shaming; Speaking Anxiety